CGIAR Foresight Initiative: New online training materials on economic modeling. Building individual and institutional modeling capacity that is sustainable over time - McCluskey, Alyssa; Schuetz, Tonya; Enahoro, Dolapo; Tierfelder, Karen; Anisimova, Evgeniya (2024)
Over the past three years, the CGIAR Research Initiative on Foresight has been working with partners to strengthen their capacity to understand and use foresight metrics and tools, and to use foresight results to shape decision-making. This includes jointly identifying key foresight training needs; developing ways to scale the use of integrated foresight tools, data, and analysis; building capacity in these tools and methods; and monitoring key outcomes and impacts to support learning and allow for course adjustments.